Evaluation of the Sewing Training Program at LKP Dessy using Kirkpatrick Evaluation Model - Sendy Romadhona; Hendra Dedi Kriswanto (Journal of Practice Learning and Educational Development, 2026)
This study evaluates the garment sewing training program at LKP Dessy using the Kirkpatrick evaluation model. The garment industry, a strategic labor-intensive sector in Indonesia, employed 473,594 workers in 2013 and absorbed 3.73 million in 2019. However, significant gaps persist between industry demands and local workforce readiness. The research employed qualitative descriptive approach to assess training effectiveness across all four Kirkpatrick levels. Data were collected through interviews with five informants (trainees, instructors, and institutional head), field observations, and documentation review. Data analysis followed Miles And Huberman’s interactive model, encompassing data reduction, data display, and conclusion. Results showed that Level 1 (Reaction) revealed highly positive participant satisfaction with instructor quality, curriculum relevance, and program organization. Level 2 (Learning) confirmed significant achievements in garment construction knowledge, positive work attitudes, and technical skills mastery. Level 3 (Behavior) demonstrated successful skill transfer to work environments with improved performance standards. Level 4 (Results) showed over 90% participant competency achievement, 100% graduate employment placement at partner companies, and enhanced economic independence. The findings demonstrate that LKP Dessy's garment sewing training program effectively develops marketable vocational skills and creates employment opportunities, serving as a model for vocational training institutions.